MONTE MOLIÃO CETARIAE (LAGOS, PORTUGAL) - Bargão, Patricia (Rei Cretariae Romanae Fautorum Acta, 2024)
This preliminary study presents the results of the emergency intervention carried out in 2007 on Monte Molião Street (Lagos). We present the results of the archaeological work in the context of the project “Urbanização de loteamento em terreno sito no Moleão – Lagos”, within the systematic archaeological works carried out by the company Palimpsesto Lda. The emergency work had to be undertaken due to the construction of several inhabitation buildings and an infraset of accessibility and leisure structures. The archaeological work was done in five distinct phases, with the results of previous interventions having partially been published.